2017
DOI: 10.1186/s13750-017-0103-1
|View full text |Cite
|
Sign up to set email alerts
|

How are biodiversity and dispersal of species affected by the management of roadsides? A systematic map

Abstract: Background: In many parts of the world, roadsides are regularly managed for traffic-safety reasons. Hence, there are similarities between roadsides and certain other managed habitats, such as wooded pastures and mown or grazed grasslands. These habitats have declined rapidly in Europe during the last century. For many species historically associated with them, roadsides may function as new primary habitats or as dispersal corridors in fragmented landscapes. Current recommendations for roadside management to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…Following a suggestion from the Swedish Board of Agriculture, we recently performed systematic mapping of the available knowledge on how roadside management affects biodiversity and the dispersal of species [18]. Since we wanted to look for evidence on general patterns of management effects, we made a global survey with no particular focus on Scandinavian conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Following a suggestion from the Swedish Board of Agriculture, we recently performed systematic mapping of the available knowledge on how roadside management affects biodiversity and the dispersal of species [18]. Since we wanted to look for evidence on general patterns of management effects, we made a global survey with no particular focus on Scandinavian conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the generation of more robust approaches to quantifying impacts, greater usage of simpler, less robust designs persists. Three systematic maps on the biodiversity impacts of different threats and management interventions found that a low proportion of studies used BACI (6-29%) and BA designs (3-37%), but many more used CI designs (48-89%) (Bernes et al 2015, Bernes et al 2017, Papathanasopoulou et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Since current recommendations for roadside management to promote diversity largely draw on studies of semi-natural grasslands, we will also investigate whether our findings differ from those on semi-natural grasslands. Our review will largely be based on studies selected from a systematic map of the evidence on how roadside management affects biodiversity and the dispersal of species along roadsides [21]. We will apply no geographical restrictions when collecting and analysing the evidence.…”
Section: Objectivesmentioning
confidence: 99%
“…We recently performed systematic mapping of the available evidence on how roadside management affects biodiversity and the dispersal of species [21]. In the protocol for the systematic map [20], we provided a general background on biodiversity effects of roadside management, presented the rationale for the mapping initiative, and described the methods that we intended to use.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation